P3.302 Sexual Health Experience and Knowledge of Human Papillomavirus (HPV) and Chlamydia in Young Women Recruited Via Social Networking Sites. (13th July 2013) - Garland, S M; Gunasekaran, B; Ahmed, N; Fenner, Y; Jayasinghe, Y; Moore, E; Fletcher, A; Tabrizi, S; Wark, J
Abstract : Background: Monitoring sexual health of young Australian women is a major research priority since introduction of the federally funded HPV vaccination programme, plus screening programmes for chlamydia. Social networking sites (SNS), commonly used by young people, present an opportunity for innovative recruitment modalities. We assessed young women's knowledge and experience of chlamydia, HPV, HPV vaccines and cervical cytology (Pap smears) utilising Facebook Method: This was part of a feasibility study assessing use of Facebook to recruit subjects for a larger prospective health study, the Young Female Health Initiative (YFHI). Women 16 to 25 years, from Victoria, Australia were eligible to participate. An advertisement was placed on Facebook for 6 months and visible to a random sample of eligible women. Women clicking on the advertisement were redirected to our website, then contacted and asked to complete a survey at the YFHI study centre, or the questionnaire online. The survey contained demographic questions, plus sexual health questions. Results: We enrolled 426 respondents, of whom 278 completed the survey (50% study centre, 50% online). Respondents' socioeconomic and geographical distribution (urban, regional, rural) were representative of the target population; those > 18 years were more likely to enrol than 16–17 year olds (p < 0.05). Overall, 76% had been sexually active, median age of coitarche was 16.9 years [CI 16.6–17.2], 63% had heard of HPV: of these, 73% knew HPV is sexually acquired and 94% that it causes cancer. 78% had heard of chlamydia: those who were sexually active were more likely to know of chlamydia than were virgins (p < 0.01), while 63% knew it could cause chronic pelvic pain, and 86% that it could cause infertility. This recruitment method also was cost-effective ($USD 20 per compliant participant). Conclusions: SNS is an effective recruitment strategy to engage young women in sexual health research